Findings of the signal approach for financial monitoring in Kazakhstan - Klaus Abberger; Wolfgang Nierhaus; Shynar Shaikh (Center for Economic Studies and ifo Institute (CESifo), 2009)
This study concentrates on the signal approach for Kazakhstan. It focuses on the properties of individual indicators prior to observed currency crises. The indicators are used to build composite indicators. An advanced approach uses principal components analysis for the construction of composite indicators. Furthermore, the common signal approach is improved by robust statistical methods. The estimation period reaches from 1997 to 2007. It is shown that most of the composite indicators are able to flag the reported crises at an early stage. In a second step it is checked whether the most recent crisis in 2009 is signalled in advance.
Keywords: E32; E37; E59; 330; currency crises; leading economic indicators; signal approach; Kazakhstan; Währungskrise; Wirtschaftsindikator; Prognoseverfahren; Frühwarnsystem; Kasachstan